2009
DOI: 10.1038/sj.bjc.6605185
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of invasive markers (uPA, CD44) and multiple drug-resistance proteins (MDR1, MRP2) is correlated with epithelial ovarian cancer progression

Abstract: BACKGROUND: Invasion and metastases of cancer cells and the development of resistance to anticancer therapies are the main causes of treatment failure and mortality in cancer patients. METHODS: We evaluated invasive markers of urokinase plasminogen activator (uPA) and CD44 and multiple drug-resistance (MDR) markers of MDR1 and MRP2 in four epithelial ovarian cancer (EOC) cell lines, primary tumours (n ¼ 120) and matched metastatic lesions (n ¼ 40) by immunofluoresence labelling. We correlated uPA and CD44 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…Indeed, pharmacokinetic studies indicated that while following IP free drug administration, the plasma concentrations peaked in 6 hrs and were almost negligible at 24 hrs, after IP ONCOFID-P there was a striking increase in drug plasma levels which plateaued within 24 hrs, lasted up to 48 hrs, and declined slowly in the following days, returning to basal levels only at 120 hrs [19]. Thus, it is very likely that the IP injected bioconjugate remains in the peritoneal cavity allowing a direct, selective and long-lasting (several days) interaction with ovarian cancer cells widely expressing the CD44 receptor [14,31], so maximizing drug uptake and therapeutic effectiveness. Further studies on tumor drug accumulation are needed to definitively confirm this advantage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, pharmacokinetic studies indicated that while following IP free drug administration, the plasma concentrations peaked in 6 hrs and were almost negligible at 24 hrs, after IP ONCOFID-P there was a striking increase in drug plasma levels which plateaued within 24 hrs, lasted up to 48 hrs, and declined slowly in the following days, returning to basal levels only at 120 hrs [19]. Thus, it is very likely that the IP injected bioconjugate remains in the peritoneal cavity allowing a direct, selective and long-lasting (several days) interaction with ovarian cancer cells widely expressing the CD44 receptor [14,31], so maximizing drug uptake and therapeutic effectiveness. Further studies on tumor drug accumulation are needed to definitively confirm this advantage.…”
Section: Discussionmentioning
confidence: 97%
“…HA receptors (CD44, RHAMM) are overexpressed in a wide variety of cancers including ovarian tumours [12][13][14]. Targeting of anti-cancer agents to tumour cells and tumour metastases can thus be accomplished by receptor-mediated uptake of bioconjugates of anticancer agents and HA, followed by the release of free drugs through the degradation of HA in cell compartments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct interactions, there were another 10 proteins/genes in network which indirectly interacted with HNF1B; among those, 6 proteins/genes including REL (55,56), CRCC2 (57), PMS2 (58), ZC3H11A (10), FOXA1 (59) and RAD51D (60) have been proven to be associated with drug resistance in ovarian and other cancers. For example, REL contributes directly to elevated uPA gene expression in human ovarian cancer cells (55), thereby promoting the multiple functions of uPA during tumor growth and metastasis, including drug resistance (56).…”
Section: Resultsmentioning
confidence: 99%
“…We excluded those articles from our meta-analysis for the following reasons: a) Non-association studies were performed, b) Researchers in those articles did not carry out histopathologic analysis or intensive clinical and imaging follow-up for at least 6 months, c) There were not association studies for other kinds of diseases d), They were review articles and no original data were reported, e) Data could not be extracted, and/or f) The data in certain articles were repeated from the same or similar population. After extensively reviewing the literature, we eventually identified a total of 8 studies with 957 patients, who met the inclusion criteria for our meta-analysis (Sillanpää et al, 2003;Chen et al, 2009a;Jiang and Chen, 2010;Steffensen et al, 2011;Li et al, 2012;Gao et al, 2015;Wang et al, 2015;Zhu et al, 2015) . Five of these studies reported the correlation of CD44 expression with the OS for ovarian cancer patients, which was assessed using the Kaplan-Meier method.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Interestingly, in recent years, it has been found that CD44 can be reliably used as a marker to identify CSCs and serve as a prognostic factor for a variety of human cancers (Ricardo et al, 2011;Wakamatsu et al, 2012;de Beça et al, 2013). However, the correlations between CD44 and the clinicopothological features and prognosis of ovarian cancer are still not clear (Sillanpää et al, 2003;Chen et al, 2009a;Gao et al, 2015;Wang et al, 2015). In this study, we performed a systematic review of the published literature and conducted a meta-analysis of the included studies to examine the association of CD44 expression with the clinicopathological features and the prognosis of ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%